Heart Rate Variability and Psychometric Analysis in Patients with Hyperactive Heart Fire Syndrome - Oliverio Medina Martínez; Ruben Fossion; Yolanda García Piceno; Rosa E. Lopez-Gomez; Emma López-Espinosa; Ismael Jiménez-Estrada; Salvador Quiroz-González (Medical Association of Pharmacopuncture Institute, 2021)
Background : Hyperactive heart fire syndrome is characterized by anxiety, insomnia, dream-disturbed sleep, tongue ulcers, heat in the hands, and palpitations. However, syndrome differentiation is often subjective due to a lack of objective, quantifiable variables. Objectives: To identify changes in heart rate variability (HRV) and psychometric analysis in patients with hyperactive heart fire syndrome. Methods : Healthy controls (n = 33) were compared to patients with hyperactive heart fire syndrome (n = 48) from the Integrative University Clinic of the State University of Ecatepec Valley (CIU-UNEVE). Physiological outcome measures included heart rate (HR), the standard deviation of the normal-to-normal heartbeat intervals (SDNN), low (LF) and high frequency (HF) power, and the LF/HF ratio. Psychometric outcome measures included the Athens Insomnia Scale (AIS) and the Hamilton Anxiety Rating Scale (HARS). Results : Compared to controls, hyperactive heart fire patients had higher HR (9.6 ± 2.62%), LF (22 ± 4.21%) and LF/HF ratio (23 ± 3.14%), and lower SDNN (21 ± 2.33%) and HF (18 ± 4.61%). Patients showed increased anxiety, both with somatic (33 ± 11.2%) and psychic symptoms (39 ± 10.5%) with more difficulty falling asleep (47 ± 9.9%) and diurnal impact of sleep (31 ± 9.6%). Conclusion : Hyperactive heart fire patients may have a sympathovagal imbalance due to a reduced parasympathetic tone and/or adominant sympathetic tone, which may be at the origin of the observed symptoms of insomnia and anxiety.